(E)‐2‐Benzylidene‐4‐phenyl‐1, 3‐diselenole ameliorates signals of renal injury induced by cisplatin in rats. Issue 1 (10th December 2012) - Bortolatto, Cristiani F.; Wilhelm, Ethel A.; Roman, Silvane S.; Nogueira, Cristina W.
ABSTRACT: The present study investigated the protective role of antioxidant ( E )‐2‐benzylidene‐4‐phenyl‐1, 3‐diselenole (BPD), an organoselenium compound, against the renal injury induced by cisplatin in rats. Canola oil or BPD (50 mg kg −1 ) was administered orally by gavage once a day for 6 days to rats. The first dose of BPD was given 24 h before a single intraperitoneal injection of saline or cisplatin (7 mg kg −1 ). At day 7, animals were killed and parameters related to renal injury were determined. The histological analysis showed that cisplatin caused renal injury in rats, which was accompanied by an increase in urea and creatinine levels in plasma. The increase of plasma creatinine levels negatively correlated with renal antioxidant defenses including ascorbic acid (AA) and reduced glutathione (GSH) content as well as glutathione S ‐transferase (GST), glutathione peroxidase (GPx) and catalase (CAT) activities. As revealed by histological analysis, BPD ameliorated tubular injury in rat kidney and reduced plasma markers altered by cisplatin. The administration of BPD to rats attenuated the reduction of renal AA and GSH content in animals exposed to cisplatin. The decrease of GST activity, but not GPx and CAT activities, in rats exposed to cisplatin was totally reversed by BPD administration. BPD was also effective in attenuating the inhibition of a sulfhydryl enzyme sensitive to oxidative stress, δ ‐aminolevulinic dehydratase, in kidneys of rats exposed to cisplatin. The present study demonstrated that BPD reduced renal injury induced by cisplatin in rats and this effect seems to be related to antioxidant mechanisms. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The protective effect of ( E )‐2‐benzylidene‐4‐phenyl‐1, 3‐diselenole (BPD) on renal injury induced by cisplatin in rats was investigated. BPD ameliorated renal injury and reduced plasma markers altered by cisplatin. BPD attenuated the reduction of renal AA and GSH content induced by cisplatin. The decrease of GST activity, but not GPx and CAT activities, in rats exposed to cisplatin was reversed by BPD. BPD was effective in attenuating the inhibition of δ ‐aminolevulinic dehydratase in kidneys of rats exposed to cisplatin.